2005
DOI: 10.1298/jjpta.8.21
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Health-Related Quality of Life Outcomes Following Cardiac Rehabilitation after Cardiac Surgery

Abstract: Abstract. We investigated the changes of an 8-week cardiac rehabilitation (CR) program on physiological outcomes and health-related quality of life (HRQL) in Japanese cardiac surgery patients. Subjects were 47 consecutive outpatients (32 men, 15 women; mean age 59.4 ± 12.6 years) recovering from cardiac surgery. Patients performed both aerobic exercise on a treadmill at anaerobic threshold intensity and moderate resistance training 2 days per week, 60 min per session, from 1 to 3 months after cardiac surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…Another study also indicated that improvement of psychological outcomes following phase II CR was similar to that of HRQOL in patients undergoing coronary artery bypass grafting and valve replacement [5]. There were significant increases in average SF-6D utility scores from 1 to 3 months in both groups (Table 2).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Another study also indicated that improvement of psychological outcomes following phase II CR was similar to that of HRQOL in patients undergoing coronary artery bypass grafting and valve replacement [5]. There were significant increases in average SF-6D utility scores from 1 to 3 months in both groups (Table 2).…”
Section: Discussionmentioning
confidence: 76%
“…Physiological outcomes were also previously reported after cardiac surgery in patients undergoing coronary artery bypass grafting and valve replacement [5][6][7][8]. The reported goals of cardiac rehabilitation (CR) for these patients are to improve exercise capacity, reduce coronary risk factors, improve health-related quality of life (HRQOL), and reduce subsequent cardiac events, sudden death, all-cause mortality, and hospitalization costs [5][6][7][8][9]. However, with regard to the economic evaluation of hospital costs, several previous studies suggested that health utility, which can be assessed by several preference-based utility measures, is an important measure in the analysis of cost effectiveness in health care [10][11][12][13].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations